Delphi study to identify key features of community-based child and adolescent mental health services in the East of England. Issue 6 (19th June 2019) - Howarth, Emma; Vainre, Maris; Humphrey, Ayla; Lombardo, Chiara; Hanafiah, Ainul Nadhirah; Anderson, Joanna K; Jones, Peter B
Abstract : Objective: To identify priorities for the delivery of community-based Child and Adolescent Mental health Services (CAMHS). Design: (1) Qualitative methods to gather public and professional opinions regarding the key principles and components of effective service delivery. (2) Two-round, two-panel adapted Delphi study. The Delphi method was adapted so professionals received additional feedback about the public panel scores. Descriptive statistics were computed. Items rated 8–10 on a scale of importance by ≥80% of both panels were identified as shared priorities. Setting: Eastern region of England. Participants: (1) 53 members of the public; 95 professionals from the children's workforce. (2) Two panels. Public panel: round 1, n=23; round 2, n=16. Professional panel: round 1, n=44; round 2, n=33. Results: 51 items met the criterion for between group consensus. Thematic grouping of these items revealed three key findings: the perceived importance of schools in mental health promotion and prevention of mental illness; an emphasis on how specialist mental health services are delivered rather than what is delivered (ie, specific treatments/programmes), and the need to monitor and evaluate service impact against shared outcomes that reflect well-being and function, in addition to the mere absence of mental health symptoms or disorders. Conclusions: Areas of consensus represent shared priorities for service provision in the East of England. These findings help to operationalise high level plans for service transformation in line with the goals and needs of those using and working in the local system and may be particularly useful for identifying gaps in ongoing transformation efforts. More broadly, the method used here offers a blueprint that could be replicated by other areas to support the ongoing transformation of CAMHS.